The reality of e-learning from the point of view of teachers and students in Iraqi universities (Journal of the College of Basic Education, 2022)
The current research aims to identify the reality of e-learning from the point of view of teachers and students in Iraqi universities. The two approaches, the survey, adopted for their research, as the sample of the researches would be from (100) teaching and teaching from the Faculty of Basic Education /the Vocalist University, and (400) students and a student from the Faculty of Basic Education /The Vaccine University, the second year of the year (2022) . The research tool was prepared, which are: the first discipline is directed to teaching, around the occurrence of electronic composition consisting of (24) paragraphs, and the fixed account was used by using the alpha - Caronbakh, as well as the value of the stability transactions (0.86), and the second one for the second to appoint (0.86). paragraph, and the stability was calculated using the alpha-Cronbach equation, where the value of the stability coefficient was (0.87). The results showed that the degree of teachers’ appreciation of the reality of e-learning in Iraqi universities ranged between (weak and large), while the degree of students’ appreciation of the reality of e-learning ranged between (medium and large), and several recommendations were reached, the most important of which is training teachers and students on the skills of using e-learning.